A Phase 1, Open‐Label Study to Evaluate the Effect of Food and Concomitant Itraconazole Administration on the Pharmacokinetics of AMG 986 in Healthy Subjects. Issue 7 (5th March 2022) - Trivedi, Ashit; Mather, Omar; Vega, Silvia; Hutton, Shauna; Hellawell, Jennifer; Lee, Edward
Abstract: This phase 1, open‐label study evaluated the effect of food and administration of the cytochrome P450 3A4 and P‐glycoprotein inhibitor itraconazole (ITZ) on the pharmacokinetics of AMG 986. In cohort 1, 12 healthy subjects received a single oral dose of AMG 986 200 mg ± food on days 1 and 10. In cohort 2, 15 healthy subjects received oral ITZ 200 mg once daily on days 8 to 15 and a single oral dose of AMG 986 10 mg on days 1 and 11. The geometric least squares mean ratios of fed/fasted for AMG 986 maximum observed concentration (Cmax ) and area under the plasma concentration–time curve from time 0 to infinity (AUCinf ) were 0.76 (90%CI, 0.61‐0.95) and 1.07 (90%CI, 0.94‐1.22), respectively. The geometric least squares mean ratios of AMG 986 10 mg plus ITZ 200 mg/AMG 986 10 mg alone for AMG 986 Cmax and AUCinf were 1.36 (90%CI, 1.25‐1.48) and 5.13 (90%CI, 4.71‐5.59), respectively. Overall, 3 subjects experienced mild treatment‐related adverse events; there were no serious or fatal adverse events. In conclusion, food had no apparent effect on the exposure of AMG 986 200 mg; therefore, food restrictions are not required. Potent cytochrome P450 3A4 and/or P‐glycoprotein inhibitors may warrant AMG 986 dose reduction and should be coadministered with caution in patients with heart failure treated with AMG 986.